POTENSI TANAMAN DI TAMAN NASIONAL PULAU JAWA SEBAGAI SUMBER BAKTERI PENGHASIL ANTIBIOTIK - Sri Yuwantiningsih; Sebastian Margino; Subagus Wahyuono (Jurnal Teknosains, 2015)
Bacterial endophytes in trees are potential source to obtain new antibiotic producers that have not been widely studied until now. This study aims to obtain bacterial endophytes isolates in the tissue of twig trees in National Park Banten, Indonesia Germplasm Garden (The Bogor Botanical Gardens), Cilacap Nusakambangan Island, Kaliurang National Park, Meru Betiri National Park Jember, and Baluran National Park, Situbondo. This selection was based on the growth ability in liquid nutrient, GY (glucose and yeast-extract), and antibiotic-3, and the ability to obstruct indicator microbes, such as Bacillus subtilis, Candida albicans, and Fusarium oxysporum. The selection result is obtained eight isolates that have inhibitory effect more than 4, such as BIN-1, KLP-1, OOH-1, STG-1, CMB-2, STL-1, MTG-1, and PPH-1. Based on chromatography method on various eluents, it is obtained three superior isolates, i.e OOH-1 ,STG-1, and CMB-2. Thus, this shows that bacterial endophytes in trees constitute potential sources for screening new antibiotic producers.